2013
DOI: 10.1016/j.stemcr.2013.10.009
|View full text |Cite|
|
Sign up to set email alerts
|

Cell-Cycle Control of Developmentally Regulated Transcription Factors Accounts for Heterogeneity in Human Pluripotent Cells

Abstract: SummaryHeterogeneity within pluripotent stem cell (PSC) populations is indicative of dynamic changes that occur when cells drift between different states. Although the role of metastability in PSCs is unclear, it appears to reflect heterogeneity in cell signaling. Using the Fucci cell-cycle indicator system, we show that elevated expression of developmental regulators in G1 is a major determinant of heterogeneity in human embryonic stem cells. Although signaling pathways remain active throughout the cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
179
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(196 citation statements)
references
References 41 publications
14
179
1
2
Order By: Relevance
“…PP1 has proven to be a potent tool to regulate the pluripotent G1 phase, as it enhances the hypophosphorylated state of Rb and enriches cells in the early G1 phase before directed differentiation. Our findings also support recent work suggesting that the G1 phase of the cell cycle may play an important role in enhancing the differentiation of hPSCs (Sela et al, 2012;Pauklin and Vallier, 2013;Singh et al, 2013). Given its role in regulating Rb and the cell cycle, PP1 could also be a useful tool in controlling the tumorigenicity of pluripotent stem cells and their differentiated progeny to enhance their therapeutic utility (Ben-David and Benvenisty, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…PP1 has proven to be a potent tool to regulate the pluripotent G1 phase, as it enhances the hypophosphorylated state of Rb and enriches cells in the early G1 phase before directed differentiation. Our findings also support recent work suggesting that the G1 phase of the cell cycle may play an important role in enhancing the differentiation of hPSCs (Sela et al, 2012;Pauklin and Vallier, 2013;Singh et al, 2013). Given its role in regulating Rb and the cell cycle, PP1 could also be a useful tool in controlling the tumorigenicity of pluripotent stem cells and their differentiated progeny to enhance their therapeutic utility (Ben-David and Benvenisty, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with earlier reports showing that developmental genes are primed for transcription in G1 phase (Singh et al, 2013(Singh et al, , 2015. Increased transcription as cells transition into G1 phase is thought to localize at genomic regions pre-marked with H3K27ac.…”
Section: Entry To and Exit From G1 Phasesupporting
confidence: 93%
“…This is an intriguing observation because it establishes a level of dynamic epigenetic regulation at developmental genes that was not previously appreciated. Consistent with changes in H3K4me3 in G1 phase, developmental genes become transcriptionally competent (Singh et al, 2013). The study suggests that developmental genes are primed for activation each time they go through G1 phase but are not activated unless the appropriate signaling networks are also active.…”
Section: Cell Fate Decisions Are Linked To G1-phase Progression In Pscsmentioning
confidence: 56%
“…The cell cycle is known to have wide-ranging effects on cellular physiology 26,27 and can modulate both differentiation and gene expression profiles 28 (Fig. 1a).…”
Section: Cell Cycle Variation Affects Global Gene Expressionmentioning
confidence: 99%
“…1a). Cells that are analyzed during development are likely to be in different stages of the cell cycle 28 . When we examined sets of genes whose expression is known to be associated with different cell-cycle stages, we observed that their expression levels varied considerably among single cells (Supplementary Fig.…”
Section: Cell Cycle Variation Affects Global Gene Expressionmentioning
confidence: 99%